2015
DOI: 10.1016/j.appet.2015.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Comfort eating, psychological stress, and depressive symptoms in young adult women

Abstract: a b s t r a c tLittle is known about whether comfort eating actually functions to reduce psychological stress. In addition, the effectiveness of comfort eating may be particularly relevant in the context of depression, but no study has tested whether comfort eating processes might depend on severity of depressive symptomology. This study tested 1) whether greater comfort eating statistically buffers the relationship between adverse life events and perceived psychological stress at age 18e19, and 2) whether pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 41 publications
2
33
1
6
Order By: Relevance
“…In relation to eating, stress driven eating is widely considered as contributing to weight gain [42, 43]. Stress induced eating among nurses may be psychologically driven, whereby eating offers comfort and relief from a preceding aversive experience [44]. Previous research has also revealed that individuals who use food as comfort frequently report difficult childhood family relationships characterised by loneliness [45].…”
Section: Discussionmentioning
confidence: 99%
“…In relation to eating, stress driven eating is widely considered as contributing to weight gain [42, 43]. Stress induced eating among nurses may be psychologically driven, whereby eating offers comfort and relief from a preceding aversive experience [44]. Previous research has also revealed that individuals who use food as comfort frequently report difficult childhood family relationships characterised by loneliness [45].…”
Section: Discussionmentioning
confidence: 99%
“…The cross-sectional nature of the study does not allow for inference on temporal ordering. For example, previous research indicates that depression may lead to changes in dietary patterns, including eating comfort foods, which tend be calorie-dense foods high in sugar and fat (Finch & Tomiyama, 2015). However, it should be noted that previous research indicates that the DII stays relatively constant over a period of 6 years (Tabung et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Most women expressed knowledge about what constitutes a healthy diet and eating pattern but at the same time they reported lacking the ability to resist unhealthy eating when faced with emotional or physical distress. Excessive eating often functions as a way to relax, as distraction or as comfort [47]. This reveals an area where interventions may improve by offering therapeutic support to help women explore the underlying reasons and thereby better cope with emotional discomfort.…”
Section: Discussionmentioning
confidence: 99%